Counselling students' experience of an online sexuality course. Issue 3 (4th May 2022) - Brammer, M. Kathryn; Goodrich, Kristopher M.
ABSTRACT: This study explored the experiences of counselling students engaged in an online sexuality course to better understand how to prepare multiculturally competent future clinicians. A phenomenological approach was adopted which reports on findings from 5 student participants enrolled in an online class. Data for the study were collected through course dairy entries in course modules and follow-up face-to-face semi-structured interviews with all participants. Four themes were identified to reflect how the researchers interpreted student's experiences of the course. These were: the importance of early life experiences; the significance of pre-course later life influences; experiences of the course; and timing. Each of these themes carried implications for the future provision of the sexuality education and training provided as part of counsellor education programmes.